The imagination of the heart « Ul » in Kabyle poetry « adekker » among women in the Ath Ouacif region: Tissugna n « wul », « lqelbb » di tmedyazt taqbaylit « Adekkeṛ » ɣer tlawin deg temnaḍt n Wat Wasif - Lachemot , Massissilia; Kherdouci , Hassina (Maalim, 2026)
them religious poetry knows as « adekker » in kabyle. The kabyle people consider « adekker » an intermediary between God and the individual. In this article, we have selected 21 adekker poems collected from women in the Ath Ouacifs region, all of which address the theme of the heart. To understand this relationship, we adopted G. Durand’s comprehensive theory of the imaginary, divided into two regimes : diurnal and nocturnal imagery. We identified the various images and symbols found in the corpus related to the heart (sadness, love, faith, ...).